2012
DOI: 10.1371/annotation/e608601c-eadd-4c11-adb2-7b605aba9c44
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Regulation of the Escherichia coli HipBA Toxin-Antitoxin System by Proteolysis

Abstract: Bacterial populations produce antibiotic-tolerant persister cells. A number of recent studies point to the involvement of toxin/antitoxin (TA) modules in persister formation. hipBA is a type II TA module that codes for the HipB antitoxin and the HipA toxin. HipA is an EF-Tu kinase, which causes protein synthesis inhibition and dormancy upon phosphorylation of its substrate. Antitoxins are labile proteins that are degraded by one of the cytosolic ATP-dependent proteases. We followed the rate of HipB degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 40 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…6B ). Because the degradation of the HipB antitoxin by Lon protease in E. coli is necessary for HipA to function as a toxin ( 37 ), we measured Caulobacter HipB2 stabilities in wild-type and lon mutant strains, under conditions of heat shock, acidic stress, and carbon starvation, and found that all three conditions stimulated HipB2 instability, which was not observed in cells lacking Lon ( Fig. 6C ).…”
Section: Resultsmentioning
confidence: 99%
“…6B ). Because the degradation of the HipB antitoxin by Lon protease in E. coli is necessary for HipA to function as a toxin ( 37 ), we measured Caulobacter HipB2 stabilities in wild-type and lon mutant strains, under conditions of heat shock, acidic stress, and carbon starvation, and found that all three conditions stimulated HipB2 instability, which was not observed in cells lacking Lon ( Fig. 6C ).…”
Section: Resultsmentioning
confidence: 99%
“…Since hip B and hip A are on the same hipBA operon, they share the same promoter and are transcribed together. The hipB protein is a transcriptional repressor of the hipBA operon and downregulates its own promoter by cooperatively binding to four operators upstream of hipBA [69,70]. Hence, the expression of the hipBA operon is autoregulated.…”
Section: Persister Cellsmentioning
confidence: 99%
“…The contiguous genes associated with IS30 potentially encode the following proteins: (i) A transcriptional regulator of the XRE family with weak similarity to the toxin-antitoxin HipB; (ii) a site specific nuclease type II (Sma-like); (iii) a hypothetical protein with similarity to a site-specific DNA-methyltransferase; (iv) a truncated hypothetical protein with similarity to the toxin-antitoxin HipA that may function with the nearby HipB to form a toxin-antitoxin module potentially involved in the production of non-growing "persister" cells that can lie dormant during stress conditions [96], including metal and oxidative stress and perhaps other stresses. The toxin-antitoxin module has also been implicated in contact inhibition of cell growth, allowing bacteria to recognize kin cells in mixed bacterial populations [97].…”
Section: Rubrerythrin and Neighborhood Genesmentioning
confidence: 99%